Intermediate film for laminated glass, and laminated glass

By controlling the width direction and thickness changes of the intermediate film for laminated glass, ensuring that its maximum curvature is below 0.010m-1, the problem of perspective deformation is solved, and better visibility and weather resistance is achieved. It is suitable for automobiles and other window glasses. application.

CN119286419APending Publication Date: 2025-01-10SEKISUI CHEMICAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411516749.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2018-09-26
Filing Date
2019-09-26
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Existing laminated glass is prone to perspective deformation when placed incline, resulting in a decrease in driver visibility. The reasons for perspective deformation have not been fully explained and are difficult to effectively suppress.

Method used

By controlling the thickness change in the width direction of the intermediate film for laminated glass, the maximum curvature is less than 0.010 m-1, and the occurrence of perspective deformation is suppressed. The specific method includes adjusting the flow direction and winding method of the intermediate film during the manufacturing process, using preferred resin materials such as polyvinyl butyral and plasticizer, combining lip-shaped method and press-roll technology to ensure uniform thickness of the intermediate film. The nature and curvature are less than 0.010m-1.

Benefits of technology

It effectively suppresses the occurrence of perspective deformation, improves the visibility and weather resistance of laminated glass, and is suitable for automotive and other window glass applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119286419A_ABST
    Figure CN119286419A_ABST
Patent Text Reader

Abstract

Provided are: an intermediate film for laminated glass, which is capable of providing laminated glass in which the occurrence of perspective deformation is suppressed; a laminated glass using the intermediate film for laminated glass; and a method for producing the intermediate film for laminated glass. The present invention is an interlayer for laminated glass in which the maximum curvature of the thickness in the width direction is 0.010 m-1 or less.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional of the application with national application number 201980050244.1 (international application number PCT / JP2019 / 037931) which entered the Chinese national phase on January 27, 2021, and invention name “Intermediate film for laminated glass and laminated glass”. Technical Field

[0002] The present invention relates to an interlayer film for laminated glass capable of providing a laminated glass in which occurrence of perspective distortion is suppressed, and to a laminated glass using the interlayer film for laminated glass. Background Art

[0003] Laminated glass obtained by sandwiching an interlayer film for laminated glass containing a thermoplastic resin such as plasticized polyvinyl butyral between two glass plates and bonding them together is widely used as window glass for automobiles, airplanes, buildings, and the like.

[0004] As an interlayer film for laminated glass, not only a single-layer structure interlayer film for laminated glass composed of only one resin layer but also a multilayer structure interlayer film for laminated glass composed of a laminate of two or more resin layers has been proposed. As a multilayer structure, by having a first resin layer and a second resin layer, and the first resin layer and the second resin layer having different properties, an interlayer film for laminated glass having various properties that are difficult to achieve with only one layer can be provided.

[0005] For example, Patent Document 1 discloses an interlayer film for laminated glass having a three-layer structure including a sound insulation layer and two protective layers sandwiching the sound insulation layer. In the interlayer film for laminated glass of Patent Document 1, excellent sound insulation is exhibited by having a sound insulation layer containing a polyvinyl acetal resin having excellent affinity with a plasticizer and a large amount of plasticizer. On the other hand, the protective layer prevents a large amount of plasticizer contained in the sound insulation layer from seeping out and reducing the adhesion between the interlayer film and the glass.

[0006] Laminated glass is required to have various optical properties depending on its use. For example, when laminated glass is used for a windshield of a car, it is important to have less perspective distortion. Perspective distortion refers to the phenomenon that when laminated glass is placed at an angle similar to the windshield, the image formed in front of the glass appears distorted. If perspective distortion exists, the driver's visibility is reduced, which sometimes causes serious obstacles to driving. However, the cause of perspective distortion has not been fully elucidated so far, and it is difficult to provide laminated glass that suppresses the occurrence of perspective distortion.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Publication No. 2007-331959 Summary of the invention

[0010] Problems to be solved by the invention

[0011] In view of the above-mentioned current situation, an object of the present invention is to provide an interlayer film for laminated glass capable of providing a laminated glass in which the occurrence of perspective distortion is suppressed, and a laminated glass using the interlayer film for laminated glass.

[0012] Means for solving problems

[0013] The present invention is an interlayer film for laminated glass, wherein the maximum curvature of the thickness in the width direction of the interlayer film for laminated glass is 0.010 m -1 the following.

[0014] The present invention is described in detail below.

[0015] The present inventors have studied the cause of perspective distortion in laminated glass and found that perspective distortion occurs because the laminated glass collects or diffuses light like a lens at a portion where the thickness in the width direction of the laminated glass changes locally.

[0016] The present inventors have studied the cause of the local thickness variation in the width direction of laminated glass, which causes perspective distortion, and have found that the cause lies in the interlayer film for laminated glass.

[0017] In the manufacturing method of laminated glass, for example, in the rubber bag method, first, the interlayer film for laminated glass unwound from the roll is cut into appropriate sizes, and the interlayer film for laminated glass is clamped between at least two glass plates to obtain a laminate, and the obtained laminate is placed in a rubber bag for decompression and suction, while degassing the air remaining between the glass plates and the interlayer film while performing pre-pressing. Then, for example, heating and pressurizing are performed in an autoclave to perform formal pressing. In addition, for example, in the clamping roller method, the laminate obtained by clamping the interlayer film for laminated glass between at least two glass plates is conveyed by a conveyor while passing through a heating zone, and after being heated to a certain temperature, it is passed through a clamping roller. Thus, the air remaining between the glass and the interlayer is scraped out and removed, and hot pressing is performed at the same time, and the air between the interlayer film and the glass of the laminate is reduced to perform pre-pressing. In the state where the air between the obtained laminate is reduced, formal bonding is performed in an autoclave at high temperature and high pressure.

[0018] It is considered that when laminated glass is manufactured by such a method, if the interlayer film for laminated glass has a local thickness variation in the width direction, the laminated glasses will bend along the interlayer film for laminated glass, and the obtained laminated glass will also have a local thickness variation in the width direction, thus causing perspective distortion.

[0019] The present inventors have conducted further in-depth studies and found that by controlling the local thickness variation in the width direction of the interlayer film for laminated glass, the maximum curvature of the thickness in the width direction is 0.010 μm. -1 Next, the present invention has been completed by being able to provide a laminated glass in which the occurrence of perspective distortion is suppressed.

[0020] The maximum curvature of the thickness in the width direction of the interlayer film for laminated glass of the present invention is 0.010 m. -1 As a result, it is possible to provide a laminated glass in which the occurrence of perspective distortion is suppressed. The maximum curvature of the thickness in the film direction of the interlayer film for laminated glass is preferably 0.008 m -1 Below, more preferably 0.007m -1 the following.

[0021] The lower limit of the maximum curvature of the thickness in the width direction of the interlayer film for laminated glass is not particularly limited, but is preferably 0.000 m when the fourth decimal place is rounded off. -1 above.

[0022] The maximum value of the thickness difference in the width direction of the interlayer film for laminated glass of the present invention measured in a 150 mm section is preferably 15 μm or less. This can provide a laminated glass with further suppressed perspective distortion. The maximum value of the thickness difference in the width direction of the interlayer film for laminated glass is more preferably 8 μm or less.

[0023] In addition, in this specification, the maximum value of the thickness difference in the width direction measured in a 150 mm section of the interlayer film for laminated glass means the difference between the maximum value and the minimum value of the thickness measurement value in the 150 mm section.

[0024] In this specification, the width direction of the interlayer film for laminated glass refers to the same planar direction orthogonal to the flow direction of the film during the manufacture of the interlayer film for laminated glass. Here, the flow direction during manufacture refers to the direction in which the raw resin composition is extruded from the extruder during the manufacture of the interlayer film for laminated glass.

[0025] It should be noted that the flow direction of the intermediate film for laminated glass during manufacture can be confirmed, for example, by the following method. That is, the flow direction can be confirmed by storing the intermediate film for laminated glass in a constant temperature chamber at 140°C for 30 minutes, and the direction in which the shrinkage rate is larger in the parallel direction and the perpendicular direction of the film is the flow direction. In addition, it can also be confirmed by the winding direction of the roll of the intermediate film for laminated glass. This is because the roll of the intermediate film for laminated glass is wound along the flow direction of the film during manufacture of the intermediate film for laminated glass, so the winding direction of the roll is the same as the flow direction of the film during manufacture of the intermediate film for laminated glass.

[0026] use Figure 1 The method for measuring the maximum curvature and the maximum value of the thickness difference in the width direction of the interlayer film for laminated glass in the present invention will be described in detail.

[0027] exist Figure 1 In (a), first, the interlayer film 1 for laminated glass is pulled out from the roll 2. At this time, the pulling direction is the flow direction during the manufacture of the interlayer film for laminated glass, and the direction in the same plane orthogonal to the flow direction is the width direction. The pulled interlayer film for laminated glass is cut at a position more than 70 cm in the flow direction to obtain a test sample of 70 cm×film width (usually 1 m). The test sample is placed on a flat surface under the conditions of 20°C and 30 RH% or less, and is provided for measurement after curing for 24 hours. After curing, a micrometer (e.g., KG601B wide-range electronic micrometer manufactured by Anritsu Electric Co., Ltd.) is used to continuously measure from one end to the other end of the width direction of the test sample at a speed of 1.5 m / min, and the thickness is recorded at intervals of 0.4 mm. The thickness is measured at 20°C and 30 RH% or less.

[0028] Next, based on the obtained data of the thickness in the width direction, the maximum curvature of the thickness in the width direction of the interlayer film for laminated glass is calculated.

[0029] That is, based on the obtained data of the thickness in the width direction, the data obtained by measuring while moving 0.4 mm each time from the end of the measuring point (the original data generated every 0.4 mm) is subjected to a simple moving average process in a 40 mm interval. After the moving average process, a cubic polynomial approximation using the least squares method is prepared in each 30 mm interval while shifting the initial value by 0.4 mm each time. The curvature of the center within the interval is calculated using the function f(x) approximated by the polynomial. The curvature is calculated by the following formula (1).

[0030] Then, the maximum value of the curvature calculated in each section is obtained and is used as the maximum curvature of the thickness in the width direction of the test sample.

[0031]

Mathematical formula 1

[0032]

[0033] On the other hand, based on the obtained data of the thickness in the width direction, the maximum value of the thickness difference in the width direction of the interlayer film for laminated glass is calculated.

[0034] That is, based on the obtained data of the thickness in the width direction, the maximum drop (the difference between the point with the largest thickness and the point with the smallest thickness) in each 150 mm interval is obtained while moving 0.4 mm from the end of the measurement point. The maximum drop in each 150 mm interval in the width direction is calculated, and the largest value is taken as the maximum value of the thickness drop in the test sample.

[0035] The interlayer film for laminated glass of the present invention preferably contains a thermoplastic resin.

[0036] Examples of the thermoplastic resin include polyvinylidene fluoride, polytetrafluoroethylene, vinylidene fluoride-hexafluoropropylene copolymer, polytrifluoroethylene, acrylonitrile-butadiene-styrene copolymer, polyester, polyether, polyamide, polycarbonate, polyacrylate, polymethacrylate, polyvinyl chloride, polyethylene, polypropylene, polystyrene, polyvinyl acetal, and ethylene-vinyl acetate copolymer. Among them, polyvinyl acetal is preferred because it is easy to produce an interlayer film for laminated glass that satisfies the above-mentioned expansion ratio in the width direction and shrinkage ratio in the flow direction.

[0037] The polyvinyl acetal can be produced, for example, by acetalizing polyvinyl alcohol (PVA) with aldehyde. The saponification degree of PVA is usually in the range of 70 to 99.9 mol%.

[0038] The degree of polymerization of the polyvinyl alcohol (PVA) used to obtain the polyvinyl acetal is preferably 200 or more, more preferably 500 or more. The degree of polymerization of the polyvinyl alcohol (PVA) is further preferably 1700 or more, particularly preferably 2000 or more, preferably 5000 or less, more preferably 4000 or less, further preferably 3000 or less, further preferably less than 3000, and particularly preferably 2800 or less. The polyvinyl acetal is preferably a polyvinyl acetal resin obtained by acetalizing PVA having a degree of polymerization of at least the lower limit and below the upper limit. If the degree of polymerization is at least the lower limit, the penetration resistance of the laminated glass is further improved. If the degree of polymerization is below the upper limit, the formation of the intermediate film becomes easy.

[0039] The degree of polymerization of PVA represents the average degree of polymerization. The average degree of polymerization is determined by a method in accordance with JIS K6726 "Testing methods for polyvinyl alcohol". As the above-mentioned aldehyde, it is generally preferred to use an aldehyde having 1 to 10 carbon atoms. As the above-mentioned aldehyde having 1 to 10 carbon atoms, for example, formaldehyde, acetaldehyde, propionaldehyde, n-butyraldehyde, isobutyraldehyde, n-valeraldehyde, 2-ethylbutyraldehyde, n-hexanal, n-octanal, n-nonanal, n-decanal and benzaldehyde can be cited. Among them, n-butyraldehyde, n-hexanal or n-valeraldehyde is preferred, and n-butyraldehyde is more preferred. The above-mentioned aldehydes may be used alone or in combination of two or more.

[0040] The polyvinyl acetal resin contained in the interlayer film for laminated glass of the present invention is preferably a polyvinyl butyral resin. By using the polyvinyl butyral resin, the weather resistance of the interlayer film for laminated glass components is further improved.

[0041] The interlayer film for laminated glass of the present invention preferably contains a plasticizer.

[0042] The plasticizer is not particularly limited as long as it is a plasticizer commonly used in interlayer films for laminated glass, and examples thereof include organic plasticizers such as monobasic organic acid esters and polybasic organic acid esters, and phosphoric acid plasticizers such as organic phosphoric acid compounds and organic phosphorous acid compounds.

[0043] Examples of the organic plasticizer include triethylene glycol di-2-ethylhexanoate, triethylene glycol di-2-ethylbutyrate, triethylene glycol di-n-heptanoate, tetraethylene glycol di-2-ethylhexanoate, tetraethylene glycol di-2-ethylbutyrate, tetraethylene glycol di-n-heptanoate, diethylene glycol di-2-ethylhexanoate, diethylene glycol di-2-ethylbutyrate, and diethylene glycol di-n-heptanoate. Among these, triethylene glycol di-2-ethylhexanoate, triethylene glycol di-2-ethylbutyrate, or triethylene glycol di-n-heptanoate is preferably included, and triethylene glycol di-2-ethylhexanoate is more preferably included.

[0044] In the interlayer film for laminated glass of the present invention, the content of the plasticizer relative to the thermoplastic resin is not particularly limited. The content of the plasticizer relative to 100 parts by mass of the thermoplastic resin is preferably 25 parts by mass or more, more preferably 30 parts by mass or more, and further preferably 35 parts by mass or more, and preferably 80 parts by mass or less, more preferably 60 parts by mass or less, and further preferably 50 parts by mass or less. If the content of the plasticizer is above the lower limit, the penetration resistance of the laminated glass is further improved. If the content of the plasticizer is below the upper limit, the transparency of the interlayer film is further improved.

[0045] The interlayer film for laminated glass of the present invention preferably contains an adhesion regulator.

[0046] As the adhesion modifier, for example, an alkali metal salt or an alkaline earth metal salt is preferably used. Examples of the adhesion modifier include salts of potassium, sodium, magnesium, and the like.

[0047] Examples of the acid constituting the salt include organic acids of carboxylic acids such as octanoic acid, hexanoic acid, 2-ethylbutyric acid, butyric acid, acetic acid, and formic acid; and inorganic acids such as hydrochloric acid and nitric acid.

[0048] The interlayer film for laminated glass of the present invention may contain additives such as antioxidants, light stabilizers, modified silicone oil as an adhesion regulator, flame retardants, antistatic agents, moisture resistance agents, heat ray reflectors, heat ray absorbers, antiblocking agents, antistatic agents, colorants including pigments or dyes, etc. as needed.

[0049] The interlayer film for laminated glass of the present invention may have a single-layer structure consisting of only one resin film, or may have a multilayer structure in which two or more resin layers are stacked.

[0050] When the interlayer film for laminated glass of the present invention has a multilayer structure, by having a first resin layer and a second resin layer as two or more resin layers, and the first resin layer and the second resin layer have different properties, an interlayer film for laminated glass having various properties that are difficult to achieve with only one layer can be provided. The multilayer structure may have three or more layers, four or more layers, or five or more layers.

[0051] When the interlayer film for laminated glass of the present invention has a multilayer structure, for example, in order to improve the sound insulation of the laminated glass, an interlayer film for laminated glass having excellent sound insulation (hereinafter also referred to as "sound insulation interlayer film") can be mentioned, in which the first resin layer is used as a protective layer, the second resin layer is used as a sound insulation layer, and the sound insulation layer is sandwiched between the two protective layers. In addition, the first resin layer or the second resin layer can be a heat insulation layer containing a heat insulation agent, and the first resin layer or the second resin layer can be a light emitting layer containing a light emitting material.

[0052] Hereinafter, the sound insulating interlayer film will be described in more detail.

[0053] In the sound insulating interlayer film, the sound insulating layer has a function of imparting sound insulating properties.

[0054] The sound insulating layer preferably contains polyvinyl acetal X and a plasticizer.

[0055] The polyvinyl acetal X can be prepared by acetalizing polyvinyl alcohol with an aldehyde. The polyvinyl acetal X is preferably an acetalized product of polyvinyl alcohol. The polyvinyl alcohol is generally obtained by saponifying polyvinyl acetate.

[0056] The preferred lower limit of the degree of polymerization of the polyvinyl alcohol is 200, and the preferred upper limit is 5000. When the degree of polymerization of the polyvinyl alcohol is 200 or more, the penetration resistance of the obtained sound insulation interlayer can be improved, and when the degree of polymerization of the polyvinyl alcohol is 5000 or less, the formability of the sound insulation layer can be ensured. The more preferred lower limit of the degree of polymerization of the polyvinyl alcohol is 500, and the more preferred upper limit is 4000.

[0057] The preferred lower limit of the carbon number of the aldehyde used to acetalize the polyvinyl alcohol is 4, and the preferred upper limit is 6. By making the carbon number of the aldehyde 4 or more, it can be stably contained in a sufficient amount of plasticizer, and excellent sound insulation performance can be exerted. In addition, the leakage of the plasticizer can be prevented. By making the carbon number of the aldehyde 6 or less, the polyvinyl acetal X can be easily synthesized and the productivity can be ensured.

[0058] The aldehyde having 4 to 6 carbon atoms may be a linear aldehyde or a branched aldehyde, and examples thereof include n-butyraldehyde and n-valeraldehyde.

[0059] The preferred upper limit of the amount of hydroxyl groups in the polyvinyl acetal X is 30 mol%. By setting the amount of hydroxyl groups in the polyvinyl acetal X to 30 mol% or less, the amount of plasticizer required to exhibit sound insulation can be contained, and the exudation of the plasticizer can be prevented. The more preferred upper limit of the amount of hydroxyl groups in the polyvinyl acetal X is 28 mol%, the further preferred upper limit is 26 mol%, the particularly preferred upper limit is 24 mol%, the preferred lower limit is 10 mol%, the more preferred lower limit is 15 mol%, and the further preferred lower limit is 20 mol%.

[0060] The hydroxyl amount of the polyvinyl acetal X is a value obtained by dividing the amount of ethylene groups bonded with hydroxyl groups by the total amount of ethylene groups in the main chain as a percentage (mol %). The ethylene groups bonded with hydroxyl groups can be obtained by measuring the amount of ethylene groups bonded with hydroxyl groups of the polyvinyl acetal X by a method in accordance with JIS K6728 "Testing methods for polyvinyl butyral".

[0061] The preferred lower limit of the acetal group content of the polyvinyl acetal X is 60 mol%, and the preferred upper limit is 85 mol%. By setting the acetal group content of the polyvinyl acetal X to 60 mol% or more, the hydrophobicity of the sound insulation layer can be improved, and the plasticizer contained in an amount required for exerting the sound insulation property can prevent the plasticizer from bleeding and whitening. By setting the acetal group content of the polyvinyl acetal X to 85 mol% or less, the polyvinyl acetal X can be easily synthesized, and productivity can be ensured. The acetal group content can be determined by measuring the ethylene content of the polyvinyl acetal X to which the acetal group is bonded using a method in accordance with JIS K6728 "Testing methods for polyvinyl butyral".

[0062] The preferred lower limit of the amount of acetyl groups in the polyvinyl acetal X is 0.1 mol%, and the preferred upper limit is 30 mol%. By making the amount of acetyl groups in the polyvinyl acetal X 0.1 mol% or more, it is possible to contain a plasticizer in an amount required for exerting sound insulation, and it is possible to prevent bleeding. In addition, by making the amount of acetyl groups in the polyvinyl acetal X 30 mol% or less, it is possible to improve the hydrophobicity of the sound insulation layer and prevent whitening. The more preferred lower limit of the amount of acetyl groups is 1 mol%, the further preferred lower limit is 5 mol%, the particularly preferred lower limit is 8 mol%, the more preferred upper limit is 25 mol%, and the further preferred upper limit is 20 mol%. The amount of acetyl groups is expressed as a percentage (mol%), which is a value of the molar fraction obtained by subtracting the amount of ethylene groups bonded with acetal groups and the amount of ethylene groups bonded with hydroxyl groups from the total amount of ethylene groups in the main chain, divided by the total amount of ethylene groups in the main chain.

[0063] In particular, from the viewpoint of being able to easily contain a plasticizer in an amount required for exhibiting sound insulation properties in the sound insulation layer, the polyvinyl acetal X is preferably a polyvinyl acetal having an acetyl group content of 8 mol% or more, or a polyvinyl acetal having an acetyl group content of less than 8 mol% and an acetal group content of 68 mol% or more.

[0064] The preferred lower limit of the content of the plasticizer in the sound insulation layer is 45 parts by mass, and the preferred upper limit is 80 parts by mass, relative to 100 parts by mass of the polyvinyl acetal X. When the content of the plasticizer is 45 parts by mass or more, high sound insulation can be achieved, and when the content of the plasticizer is 80 parts by mass or less, it is possible to prevent the plasticizer from bleeding out and reducing the transparency and adhesion of the interlayer film for laminated glass. The more preferred lower limit of the content of the plasticizer is 50 parts by mass, and the further preferred lower limit is 55 parts by mass. The more preferred upper limit is 75 parts by mass, and the further preferred upper limit is 70 parts by mass.

[0065] When the cross-sectional shape of the sound insulation layer in the thickness direction is a rectangle, the preferred lower limit of the thickness is 50 μm. When the thickness of the sound insulation layer is 50 μm or more, sufficient sound insulation can be achieved. The more preferred lower limit of the thickness of the sound insulation layer is 70 μm, and the further preferred lower limit is 80 μm. It should be noted that the upper limit is not particularly limited, but in consideration of the thickness of the interlayer film for laminated glass, the preferred upper limit is 150 μm.

[0066] The sound insulation layer may have a shape having one end and another end located on the opposite side of the one end, and the thickness of the other end is greater than the thickness of the one end. The sound insulation layer preferably has a portion whose cross-sectional shape in the thickness direction is a wedge shape. In this case, the preferred lower limit of the minimum thickness of the sound insulation layer is 50 μm. By setting the minimum thickness of the sound insulation layer to be 50 μm or more, sufficient sound insulation can be achieved. The more preferred lower limit of the minimum thickness of the sound insulation layer is 80 μm, and the further preferred lower limit is 100 μm. It should be noted that the upper limit of the maximum thickness of the sound insulation layer is not particularly limited, and if the thickness of the intermediate film for laminated glass is taken into consideration, the preferred upper limit is 300 μm. The more preferred upper limit of the maximum thickness of the sound insulation layer is 220 μm.

[0067] The protective layer has the functions of preventing a large amount of plasticizer contained in the sound insulation layer from seeping out and thereby reducing the adhesion between the interlayer film for laminated glass and glass, and also providing penetration resistance to the interlayer film for laminated glass.

[0068] The protective layer preferably contains, for example, polyvinyl acetal Y and a plasticizer, and more preferably contains polyvinyl acetal Y having a larger hydroxyl group amount than that of polyvinyl acetal X and a plasticizer.

[0069] The polyvinyl acetal Y can be prepared by acetalizing polyvinyl alcohol with an aldehyde. The polyvinyl acetal Y is preferably an acetalized product of polyvinyl alcohol.

[0070] The polyvinyl alcohol is usually obtained by saponifying polyvinyl acetate. In addition, the preferred lower limit of the degree of polymerization of the polyvinyl alcohol is 200, and the preferred upper limit is 5000. By setting the degree of polymerization of the polyvinyl alcohol to be 200 or more, the penetration resistance of the interlayer film for laminated glass can be improved, and by setting the degree of polymerization of the polyvinyl alcohol to be 5000 or less, the formability of the protective layer can be ensured. The more preferred lower limit of the degree of polymerization of the polyvinyl alcohol is 500, and the more preferred upper limit is 4000.

[0071] The preferred lower limit of the carbon number of the aldehyde used for acetalizing the polyvinyl alcohol is 3, and the preferred upper limit is 4. When the carbon number of the aldehyde is 3 or more, the penetration resistance of the interlayer film for laminated glass becomes higher. When the carbon number of the aldehyde is 4 or less, the productivity of the polyvinyl acetal Y is improved.

[0072] The aldehyde having 3 to 4 carbon atoms may be a linear aldehyde or a branched aldehyde, and examples thereof include n-butylaldehyde.

[0073] The preferred upper limit of the amount of hydroxyl groups in the polyvinyl acetal Y is 33 mol%, and the preferred lower limit is 28 mol%. When the amount of hydroxyl groups in the polyvinyl acetal Y is 33 mol% or less, whitening of the interlayer film for laminated glass can be prevented. When the amount of hydroxyl groups in the polyvinyl acetal Y is 28 mol% or more, the penetration resistance of the interlayer film for laminated glass becomes high.

[0074] The preferred lower limit of the acetal group content of the polyvinyl acetal Y is 60 mol%, and the preferred upper limit is 80 mol%. By making the acetal group content 60 mol% or more, it is possible to contain a plasticizer in an amount required to exert sufficient penetration resistance. By making the acetal group content 80 mol% or less, it is possible to ensure the adhesion between the protective layer and the glass. The more preferred lower limit of the acetal group content is 65 mol%, and the more preferred upper limit is 69 mol%.

[0075] The preferred upper limit of the acetyl group amount of the polyvinyl acetal Y is 7 mol%. By making the acetyl group amount of the polyvinyl acetal Y below 7 mol%, the hydrophobicity of the protective layer can be improved to prevent whitening. The more preferred upper limit of the acetyl group amount is 2 mol%, and the preferred lower limit is 0.1 mol%. It should be noted that the hydroxyl group amount, acetal group amount and acetyl group amount of the polyvinyl acetal Y can be measured by the same method as the polyvinyl acetal X.

[0076] The preferred lower limit of the content of the plasticizer in the protective layer is 20 parts by mass, and the preferred upper limit is 45 parts by mass, relative to 100 parts by mass of the polyvinyl acetal Y. By setting the content of the plasticizer to 20 parts by mass or more, penetration resistance can be ensured, and by setting the content of the plasticizer to 45 parts by mass or less, it is possible to prevent the plasticizer from seeping out and prevent the transparency and adhesiveness of the interlayer film for laminated glass from being reduced. The more preferred lower limit of the content of the plasticizer is 30 parts by mass, and the further preferred lower limit is 35 parts by mass. The more preferred upper limit is 43 parts by mass, and the further preferred upper limit is 41 parts by mass. From the perspective of further improving the sound insulation of the laminated glass, the content of the plasticizer in the protective layer is preferably less than the content of the plasticizer in the sound insulation layer.

[0077] From the viewpoint of further improving the sound insulation of the laminated glass, the hydroxyl amount of the polyvinyl acetal Y is preferably greater than that of the polyvinyl acetal X, more preferably 1 mol% or more greater than that of the polyvinyl acetal X, further preferably 5 mol% or more greater than that of the polyvinyl acetal X, and particularly preferably 8 mol% or more greater than that of the polyvinyl acetal X. By adjusting the hydroxyl amounts of the polyvinyl acetal X and the polyvinyl acetal Y, the content of the plasticizer in the sound insulation layer and the protective layer can be controlled, and the glass transition temperature of the sound insulation layer can be lowered. As a result, the sound insulation of the laminated glass is further improved.

[0078] In addition, from the viewpoint of further improving the sound insulation of the laminated glass, the content of the plasticizer in the sound insulation layer relative to 100 parts by mass of the polyvinyl acetal X (hereinafter referred to as content X) is preferably greater than the content of the plasticizer in the protective layer relative to 100 parts by mass of the polyvinyl acetal Y (hereinafter referred to as content Y), more preferably 5 parts by mass or more than the content of the plasticizer in the protective layer relative to 100 parts by mass of the polyvinyl acetal Y, further preferably 15 parts by mass or more than the content of the plasticizer in the protective layer relative to 100 parts by mass of the polyvinyl acetal Y, and particularly preferably 20 parts by mass or more than the content of the plasticizer in the protective layer relative to 100 parts by mass of the polyvinyl acetal Y. By adjusting the content X and the content Y, the glass transition temperature of the sound insulation layer becomes lower. As a result, the sound insulation of the laminated glass is further improved.

[0079] When the cross-sectional shape of the protective layer is rectangular, the preferred lower limit of the thickness of the protective layer is 200 μm, and the preferred upper limit is 1000 μm. By setting the thickness of the protective layer to be 200 μm or more, penetration resistance can be ensured. The more preferred lower limit of the thickness of the protective layer is 300 μm, and the more preferred upper limit is 700 μm.

[0080] The protective layer may have a shape having one end and another end located on the opposite side of the one end, and the thickness of the other end is greater than the thickness of the one end. The protective layer preferably has a portion whose cross-sectional shape in the thickness direction is wedge-shaped. The thickness of the protective layer is not particularly limited as long as it is adjusted to a range in which the function of the protective layer can be exerted. However, in the case where the protective layer has concavoconvexities, in order to suppress the transfer of the concavoconvexities to the interface between the sound insulation layer in direct contact, it is preferably set thicker within a possible range. Specifically, the preferred lower limit of the minimum thickness of the protective layer is 100μm, the more preferred lower limit is 300μm, the further preferred lower limit is 400μm, and the particularly preferred lower limit is 450μm. There is no particular upper limit on the maximum thickness of the protective layer. In order to ensure that the thickness of the sound insulation layer is to a degree that can achieve sufficient sound insulation, the upper limit is substantially about 1000μm, preferably 800μm.

[0081] The interlayer film for laminated glass of the present invention may have one end and the other end located on the opposite side of the one end. The one end and the other end are end portions on both sides facing each other in the interlayer film. In the interlayer film for laminated glass of the present invention, the thickness of the other end is preferably greater than the thickness of the one end. By having such a shape in which the thickness of one end and the other end are different, the laminated glass using the interlayer film for laminated glass of the present invention can be used as a head-up display, and in this case, the generation of ghosting can be effectively suppressed. The cross-sectional shape of the interlayer film for laminated glass of the present invention may be a wedge shape. If the cross-sectional shape of the interlayer film for laminated glass is a wedge shape, by adjusting the wedge angle θ of the wedge shape according to the installation angle of the laminated glass, an image display in which the generation of ghosting is prevented can be performed in the head-up display. From the viewpoint of further suppressing ghosting, the preferred lower limit of the wedge angle θ is 0.1 mrad, the more preferred lower limit is 0.2 mrad, the more preferred lower limit is 0.3 mrad, the preferred upper limit is 1 mrad, and the more preferred upper limit is 0.9 mrad. It should be noted that, for example, when an interlayer film for laminated glass having a wedge-shaped cross-sectional shape is manufactured by extruding a resin composition using an extruder, the shape may have a minimum thickness in a region slightly inward from one end of the thin side, and a maximum thickness in a region slightly inward from one end of the thick side. (Specifically, the region slightly inward refers to a region with a distance of 0X to 0.2X from one end of the thick side or the thin side toward the inside when the distance between one end and the other end is X) In this specification, such a shape is also included in the wedge shape.

[0082] The method for producing the sound insulating interlayer is not particularly limited, and examples thereof include a method in which the sound insulating layer and the protective layer are formed into sheets by a common film-forming method such as extrusion, calendaring, or pressing, and then laminated.

[0083] The method for producing the interlayer film for laminated glass of the present invention is not particularly limited, and the interlayer film can be produced by extruding the raw resin composition from an extruder. Here, by controlling the conditions during extrusion molding, an interlayer film for laminated glass that satisfies the maximum curvature of the thickness in the width direction and the maximum value of the thickness difference in the width direction can be obtained. Here, when the surface of the interlayer film for laminated glass is embossed, it is difficult to obtain an interlayer film for laminated glass that satisfies the maximum curvature of the thickness in the width direction and the maximum value of the thickness difference in the width direction by using an embossing roller, so it is preferred to use a lip method that gives projections and depressions by designing the shape of the tube head of the die of the extruder.

[0084] More specifically, it is preferred that (1) a tube head with a straightness of 4 μm or less in the width direction of 1000 mm and a concavity of 2 μm or less in the width direction of 80 mm be used as the tube head of the extruder used in the lip method, and (2) a press roll with a cylindricality of 4 μm or less be used as the press roll. By controlling the extrusion conditions in this way, an interlayer film for laminated glass that satisfies the maximum curvature of the thickness in the width direction and the maximum value of the thickness drop in the width direction can be obtained.

[0085] A method for producing an interlayer film for laminated glass is also one of the present invention, which is a method for producing the interlayer film for laminated glass of the present invention, comprising a step of using a lip method for imparting projections and depressions to the surface of the interlayer film for laminated glass while extruding a raw resin composition from an extruder, wherein a tube head of the extruder is used that has a straightness of 4 μm or less over a width of 1,000 mm and a projection and depression of 2 μm or less over a width of 80 mm.

[0086] The thickness variation of the interlayer film for laminated glass of the present invention in the width direction is controlled so that the maximum curvature of the thickness in the width direction becomes 0.010 m. -1 Since the following adjustment is performed, the thickness variation of the laminated glass in the width direction is small. Therefore, the perspective distortion of the obtained laminated glass is extremely small.

[0087] It should be noted that the degree of perspective distortion can be evaluated by performing a distortion test.

[0088] The maximum curvature of the thickness in the width direction of the interlayer film for laminated glass in the laminated glass is 0.004 m -1 The following laminated glass is also one of the present invention as a laminated glass in which the interlayer film for laminated glass of the present invention is laminated between a pair of glass plates. By setting the maximum curvature of the thickness in the width direction of the interlayer film for laminated glass in the laminated glass to 0.004 m -1 The maximum curvature of the thickness in the width direction of the interlayer film for laminated glass in the laminated glass is more preferably 0.003 m. -1 the following.

[0089] The maximum curvature of the thickness of the laminated glass in the width direction is 0.010m -1 The following laminated glass is also one of the present invention as a laminated glass in which the interlayer film for laminated glass of the present invention is laminated between a pair of glass plates. By setting the maximum curvature of the thickness in the width direction of the laminated glass itself to 0.010 m -1 The maximum curvature of the thickness in the width direction of the laminated glass is more preferably 0.003 m. -1 the following.

[0090] It should be noted that the width direction of the laminated glass coincides with the width direction of the interlayer film for laminated glass.

[0091] The glass plate may be a commonly used transparent plate glass. For example, inorganic glass such as float plate glass, polished plate glass, patterned glass, wired plate glass, wired plate glass, colored plate glass, heat ray absorbing glass, heat ray reflecting glass, and green glass may be used. In addition, ultraviolet shielding glass having an ultraviolet shielding coating formed on the surface of the glass may be used. Furthermore, organic plastic plates such as polyethylene terephthalate, polycarbonate, and polyacrylate may be used.

[0092] As the glass plate, two or more glass plates may be used. For example, laminated glass may be a laminated glass in which the interlayer film for laminated glass of the present invention is laminated between a colored glass plate such as a transparent float glass and a raw glass. In addition, as the glass plate, two or more glass plates having different thicknesses may be used.

[0093] The method for measuring the maximum curvature of the thickness in the width direction and the maximum value of the thickness drop of the laminated glass of the present invention is substantially the same as the method for measuring the maximum curvature of the thickness in the width direction and the maximum value of the thickness drop of the interlayer film for laminated glass described above. It should be noted that the test samples were samples that were fully left to cool at 20°C and 30RH% after the manufacture of the laminated glass.

[0094] Effects of the Invention

[0095] According to the present invention, there can be provided an interlayer film for laminated glass capable of providing laminated glass in which occurrence of perspective distortion is suppressed, laminated glass using the interlayer film for laminated glass, and a method for producing the interlayer film for laminated glass. BRIEF DESCRIPTION OF THE DRAWINGS

[0096] Figure 1 It is a schematic diagram for explaining a method for measuring the maximum curvature of the thickness in the width direction of the interlayer film for laminated glass and the maximum value of the thickness difference.

[0097] Figure 2 It is a schematic diagram explaining the deformation test in the evaluation of Examples and Comparative Examples. DETAILED DESCRIPTION

[0098] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0099] (Example 1)

[0100] (1) Manufacture of interlayer films for laminated glass

[0101] Relative to 100 parts by mass of polyvinyl butyral, 40 parts by mass of plasticizer, 0.5 parts by mass of ultraviolet shielding agent and 0.5 parts by mass of antioxidant are added, and fully mixed with a mixing roller to obtain a resin composition. It should be noted that in polyvinyl butyral, the content of hydroxyl is 30 mol%, the degree of acetylation is 1 mol%, the degree of butyralization is 69 mol%, and the average degree of polymerization is 1700. As a plasticizer, triethylene glycol di-2-ethylhexanoate (3GO) is used. As an ultraviolet shielding agent, 2-(2'-hydroxy-3'-tert-butyl-5-methylphenyl)-5-chlorobenzotriazole (BASF, "Tinuvin326") is used. As an antioxidant, 2,6-di-tert-butyl-p-cresol (BHT) is used.

[0102] The obtained resin composition was extruded by an extruder to obtain a single-layer interlayer film for laminated glass having a width of 100 cm, and the interlayer film was wound into a roll.

[0103] At this time, as the extruder head used in the lip method, a head with a straightness of 4 μm over a width of 1000 mm and a concavity of 2 μm over a width of 80 mm was used. As the pressing roll, a pressing roll with a cylindricality of 3 μm was used.

[0104] The interlayer film for laminated glass is pulled out from the obtained roll, and cut at a position of 70 cm in the flow direction to obtain a test sample of 70 cm × film width (1 m). The test sample is placed on a flat surface under the conditions of 20°C and 30 RH% or less, and is cured for 24 hours before measurement. After curing, a micrometer (KG601B wide-range electronic micrometer manufactured by Anritsu Electric Co., Ltd.) is used to continuously measure from one end to the other end of the width direction of the test sample at a speed of 1.5 m / min, and the thickness is recorded at intervals of 0.4 mm. The thickness measurement is carried out under the conditions of 20°C and 30 RH% or less. Next, based on the obtained data of the thickness in the width direction, the maximum curvature of the thickness in the width direction of the interlayer film for laminated glass is calculated. First, based on the obtained data of the thickness in the width direction, the data obtained by measuring while moving 0.4 mm each time from the end of the measuring point (the original data generated every 0.4 mm) is subjected to a simple moving average process in a 40 mm interval. After the moving average process, the initial value is shifted by 0.4 mm each time, and a cubic polynomial approximation using the least squares method is prepared in each 30 mm interval. The curvature of the center in the interval is calculated using the function f(x) approximated by the polynomial. The curvature is calculated by the above formula (1). Then, the maximum value of the curvature calculated in each interval is obtained and used as the maximum curvature of the thickness in the width direction of the test sample.

[0105] On the other hand, based on the obtained data of the thickness in the width direction, the maximum value of the thickness drop in the width direction of the interlayer film for laminated glass is calculated. That is, based on the obtained data of the thickness in the width direction, the maximum drop (the difference between the point with the maximum thickness and the point with the minimum thickness) in each 150 mm section is obtained while moving 0.4 mm from the end of the measurement point. The maximum drop in each 150 mm section in the width direction is calculated, and the maximum value is taken as the maximum value of the thickness drop in the test sample.

[0106] (2) Manufacturing of laminated glass

[0107] The interlayer film for laminated glass was pulled out from the roll and cut at a position of 70 cm in the flow direction to obtain an interlayer film for laminated glass of 70 cm x film width (1 m). The interlayer film for laminated glass was placed on a flat surface at 20°C and 30 RH% or less and cured for 24 hours before being applied to laminated glass.

[0108] The interlayer film for laminated glass was laminated between two glass plates having a thickness of 1.7 mm, a width of 750 mm, and a length of 500 mm, so that the width direction of the interlayer film for laminated glass was parallel to the transverse direction of the glass plate, the flow direction of the interlayer film for laminated glass was parallel to the longitudinal direction of the glass plate, and the center of the glass plate was located at the center of the interlayer film for laminated glass. Then, the exposed interlayer film for laminated glass was cut to obtain a laminated body.

[0109] The obtained laminate is conveyed by a conveyor while passing through a heating zone, and after heating, the air remaining between the glass and the interlayer is scraped out and removed by a clamping roller, and thermocompression bonding is performed at the same time, thereby reducing the air between the interlayer film for laminated glass and the glass of the laminate and performing preliminary compression bonding. The laminate after preliminary compression bonding is formally bonded in an autoclave at high temperature and high pressure to obtain a laminated glass.

[0110] Here, the heating temperature of the heating zone was set to 220°C, the surface temperature of the glass after passing through the heating zone was set to 80°C, the heating time was set to less than 1 minute, and the clamping pressure was set to 3 kg / cm 2 The temperature in the autoclave was set to a maximum of 140°C and the maximum pressure was set to 14 kg / cm 2 The heating and pressurizing time in the autoclave was set to a maximum of 30 minutes.

[0111] For the obtained laminated glass, the maximum curvature of the thickness in the width direction of the laminated glass and the maximum curvature of the thickness in the width direction of the interlayer film for laminated glass in the laminated glass were calculated by the same method as the evaluation of the shape of the interlayer film for laminated glass described above.

[0112] (Comparative Example 1)

[0113] The same operation as in Example 1 was performed except that the tube head of the extruder used in the lip method had a straightness of 7 μm in the width direction of 1000 mm and a concavity of 2 μm in the width direction of 80 mm, and the roller had a cylindricality of 5 μm. The interlayer film for laminated glass was obtained and wound into a roll. Laminated glass was manufactured in the same manner as in Example 1.

[0114] (Comparative Example 2)

[0115] The same operation as in Example 1 was performed except that the tube head of the extruder used in the lip method had a straightness of 8 μm in the width direction of 1000 mm and a concavity of 2 μm in the width direction of 80 mm, and the roller had a cylindricality of 6 μm. The interlayer film for laminated glass was obtained and wound into a roll. In addition, laminated glass was manufactured by the same method as in Example 1, and the maximum curvature of the thickness in the width direction of the laminated glass was calculated.

[0116] (Example 2)

[0117] (1) Preparation of resin composition for protective layer

[0118] Relative to 100 parts by weight of polyvinyl butyral resin, 38.8 parts by weight of plasticizer, 0.5 parts by weight of ultraviolet shielding agent and 0.5 parts by weight of antioxidant were added, and the mixture was fully mixed with a mixing roller to obtain a protective layer resin composition. It should be noted that in polyvinyl butyral, the content of hydroxyl groups is 30 mol%, the degree of acetylation is 1 mol%, the degree of butyralization is 69 mol%, and the average degree of polymerization is 1700. As an ultraviolet shielding agent, "Tinuvin326" manufactured by BASF was used. As a plasticizer, triethylene glycol di-2-ethylhexanoate (3GO) was used. As an ultraviolet shielding agent, 2-(2'-hydroxy-3'-tert-butyl-5-methylphenyl)-5-chlorobenzotriazole (manufactured by BASF, "Tinuvin326") was used. As an antioxidant, 2,6-di-tert-butyl-p-cresol (BHT) was used.

[0119] (2) Preparation of resin composition for sound insulation layer

[0120] 68.8 parts by weight of a plasticizer was added to 100 parts by weight of a polyvinyl butyral resin, and the mixture was fully kneaded with a mixing roll to obtain a resin composition for a sound insulation layer. It should be noted that the polyvinyl butyral had a hydroxyl content of 23.3 mol%, an acetylation degree of 12.5 mol%, a butyralization degree of 64.2 mol%, and an average polymerization degree of 2300. As a plasticizer, triethylene glycol di-2-ethylhexanoate (3GO) was used.

[0121] (3) Manufacture of interlayer films for laminated glass

[0122] The resin composition for the sound insulation layer and the resin composition for the protective layer were co-extruded to obtain an interlayer film for laminated glass having a width of 100 cm and a three-layer structure in which a protective layer (average thickness 350 μm), a sound insulation layer (average thickness 100 μm), and a protective layer (average thickness 350 μm) were sequentially laminated in the thickness direction, and the film was wound into a roll. At this time, as the head of the extruder used in the lip method, a head having a straightness of 4 μm in a width direction of 1000 mm and a concavity of 2 μm in a width direction of 80 mm was used, and as the pressing roll, a pressing roll having a cylindricality of 4 μm was used.

[0123] For the obtained interlayer film for laminated glass, the average thickness in the width direction of the interlayer film for laminated glass, the maximum curvature of the thickness in the width direction, and the maximum value of the thickness difference in the width direction were calculated by the same method as in Example 1. In addition, laminated glass was manufactured by the same method as in Example 1, and the maximum curvature of the thickness in the width direction of the laminated glass and the maximum curvature of the thickness in the width direction of the interlayer film for laminated glass in the laminated glass were calculated.

[0124] (Example 3)

[0125] The extrusion conditions were set so that the cross-sectional shape of each protective layer in the thickness direction of the interlayer film for laminated glass obtained after the unevenness was given was a rectangle with a maximum thickness of 409 μm and a minimum thickness of 329 μm, the cross-sectional shape of the sound insulation layer in the thickness direction was a rectangle with a maximum thickness of 129 μm and a minimum thickness of 98 μm, and the cross-sectional shape of the interlayer film in the thickness direction was a rectangle with an average film thickness of 825 μm. In addition, the interlayer film for laminated glass was prepared by the same method as in Example 2, and the average thickness in the width direction, the maximum curvature of the thickness in the width direction, and the maximum value of the thickness difference in the width direction were calculated. In addition, laminated glass was manufactured by the same method as in Example 1, and the maximum curvature of the thickness in the width direction of the laminated glass and the maximum curvature of the thickness in the width direction of the interlayer film for laminated glass in the laminated glass were calculated.

[0126] (Example 4)

[0127] (Manufacture of interlayer film for wedge-shaped laminated glass)

[0128] The sound insulation layer resin composition and the protective layer resin composition obtained in the same manner as in Example 2 were coextruded using a coextruder to obtain an interlayer film for laminated glass having a three-layer structure of protective layer, sound insulation layer, and protective layer laminated in this order in the thickness direction, and the interlayer film was wound into a roll.

[0129] Here, the extrusion conditions were set so that the cross-sectional shape in the thickness direction of each protective layer of the laminated glass interlayer obtained after the unevenness was given was a wedge-shaped shape with a maximum thickness of 790 μm and a minimum thickness of 280 μm, the cross-sectional shape in the thickness direction of the sound insulation layer was a wedge-shaped shape with a maximum thickness of 180 μm and a minimum thickness of 90 μm, and the cross-sectional shape in the thickness direction of the entire interlayer film was a wedge-shaped shape with a maximum thickness of 1440 μm and a minimum thickness of 700 μm. The extrusion conditions were set so that the width of the entire interlayer film was 100 cm.

[0130] At this time, the temperature of the die is adjusted by setting a temperature gradient in the range of 100°C to 280°C for the lip die so that the end portion of the intermediate film with a thin thickness as a whole becomes a low temperature and the end portion of the intermediate film with a thick thickness as a whole becomes a high temperature side in the width direction. In addition, as the lip die, the gap of the lip is adjusted in the range of 1.0 to 4.0 mm. The speed difference of each roller through which the resin film discharged from the lip die passes before winding is adjusted to be less than 15%. Furthermore, the roller through which the resin film discharged from the lip die passes first is set to be lower than the die and in front of the die in the flow direction, the extrusion amount from the extruder is adjusted to 700 kg / hour, and the speed of the roller passing first is adjusted to 7 m / minute.

[0131] In addition, at this time, as the extruder head used in the lip method, a head with a straightness of 4 μm in the width direction of 1000 mm and a concavity of 2 μm in the width direction of 80 mm was used, and as the pressing roll, a pressing roll with a cylindricality of 3 μm was used.

[0132] For the obtained interlayer film for laminated glass, the average thickness in the width direction of the interlayer film for laminated glass, the maximum curvature of the thickness in the width direction, and the maximum value of the thickness difference in the width direction were calculated by the same method as in Example 1. In addition, laminated glass was manufactured by the same method as in Example 1, and the maximum curvature of the thickness in the width direction of the laminated glass and the maximum curvature of the thickness in the width direction of the interlayer film for laminated glass in the laminated glass were calculated.

[0133] (Example 5)

[0134] (1) Preparation of resin composition for color layer

[0135] Relative to 100 parts by weight of polyvinyl butyral resin, add 38.8 parts by weight of plasticizer, 0.5 parts by weight of ultraviolet shielding agent and 0.5 parts by weight of antioxidant, fully mix with mixing roller to obtain resin composition. It should be noted that in polyvinyl butyral, the content of hydroxyl is 30 mol%, the degree of acetylation is 1 mol%, the degree of butyralization is 69 mol%, and the average degree of polymerization is 1700. As a plasticizer, triethylene glycol di-2-ethylhexanoate (3GO) is used. As an ultraviolet shielding agent, 2-(2'-hydroxy-3'-tert-butyl-5-methylphenyl)-5-chlorobenzotriazole (BASF company system, "Tinuvin326") is used. As an antioxidant, 2,6-di-tert-butyl-p-cresol (BHT) is used.

[0136] Carbon black was added as a colorant to the obtained composition, and the mixture was fully kneaded with a mixing roll to obtain a resin composition for a color layer. The amount of the colorant added was set to 0.260% by mass in 100% by mass of the color resin layer.

[0137] (2) Manufacture of interlayer films for laminated glass

[0138] The obtained resin composition for the color layer, the resin composition for the sound insulation layer obtained by the same method as in Example 2, and the resin composition for the protective layer were co-extruded using a co-extruder to obtain an interlayer film for laminated glass having a five-layer structure of a protective layer, a color layer, a protective layer, a sound insulation layer, and a protective layer laminated in this order in the thickness direction, and the interlayer film was wound into a roll.

[0139] Here, the extrusion conditions were set so that, in the interlayer film for laminated glass obtained after the unevenness was imparted, the cross-sectional shape in the thickness direction of each of the protective layer and the color layer was a rectangle with a maximum thickness of 423 μm and a minimum thickness of 322 μm, the cross-sectional shape in the thickness direction of the sound insulation layer was a rectangle with a maximum thickness of 123 μm and a minimum thickness of 96 μm, and the cross-sectional shape in the thickness direction of the entire interlayer film was a rectangle with an average film thickness of 810 μm.

[0140] At this time, the temperature of the die is adjusted by setting a temperature gradient in the range of 100°C to 280°C for the lip die so that the end portion of the intermediate film with a thin thickness as a whole becomes a low temperature and the end portion of the intermediate film with a thick thickness as a whole becomes a high temperature side in the width direction. In addition, as the lip die, the gap of the lip is adjusted in the range of 1.0 to 4.0 mm. The speed difference of each roller through which the resin film discharged from the lip die passes before winding is adjusted to be less than 15%. Furthermore, the roller through which the resin film discharged from the lip die passes first is set to be lower than the die and in front of the die in the flow direction, the extrusion amount from the extruder is adjusted to 700 kg / hour, and the speed of the roller passing first is adjusted to 7 m / minute.

[0141] In addition, at this time, as the extruder head used in the lip method, a head with a straightness of 4 μm in the width direction of 1000 mm and a concavity of 2 μm in the width direction of 80 mm was used, and as the pressing roll, a pressing roll with a cylindricality of 3 μm was used.

[0142] For the obtained interlayer film for laminated glass, the average thickness in the width direction of the interlayer film for laminated glass, the maximum curvature of the thickness in the width direction, and the maximum value of the thickness difference in the width direction were calculated by the same method as in Example 1. In addition, laminated glass was manufactured by the same method as in Example 1, and the maximum curvature of the thickness in the width direction of the laminated glass and the maximum curvature of the thickness in the width direction of the interlayer film in the laminated glass were calculated.

[0143] (Comparative Example 3)

[0144] The same operation as in Example 2 was performed except that the tube head of the extruder used in the lip method had a straightness of 10 μm in the width direction of 1000 mm and a concavity of 2 μm in the width direction of 80 mm, and the roller had a cylindricality of 6 μm. The interlayer film for laminated glass was obtained and wound into a roll. Laminated glass was manufactured in the same manner as in Example 2.

[0145] (Comparative Example 4)

[0146] The same operation as in Example 2 was performed except that the tube head of the extruder used in the lip method had a straightness of 11 μm in the width direction of 1000 mm and a concavity of 2 μm in the width direction of 80 mm, and the roller had a cylindricality of 8 μm. The interlayer film for laminated glass was obtained and wound into a roll. Laminated glass was manufactured in the same manner as in Example 2.

[0147] (evaluate)

[0148] The interlayer films for laminated glass obtained in the Examples and Comparative Examples were evaluated by the following methods.

[0149] (1) Manufacture of sample laminated glass

[0150] The interlayer film for laminated glass was pulled out from the roll and cut at a position of 70 cm in the flow direction to obtain an interlayer film for laminated glass of 70 cm x film width (1 m). The interlayer film for laminated glass was placed on a flat surface at 20°C and 30 RH% or less and cured for 24 hours before being applied to laminated glass.

[0151] The interlayer film for laminated glass was laminated between two glass plates with a thickness of 2 mm, a width of 750 mm, and a length of 500 mm, so that the width direction of the interlayer film for laminated glass was parallel to the transverse direction of the glass plate, the flow direction of the interlayer film for laminated glass was parallel to the longitudinal direction of the glass plate, and the center of the glass plate was located at the center of the interlayer film for laminated glass. Then, the exposed interlayer film for laminated glass was cut to obtain a laminated body.

[0152] The obtained laminate is conveyed by a conveyor while passing through a heating zone, and after heating, the air remaining between the glass and the interlayer is scraped out and removed by a clamping roller, and thermocompression bonding is performed at the same time, thereby reducing the air between the interlayer film for laminated glass and the glass of the laminate and performing preliminary compression bonding. The laminate after preliminary compression bonding is formally bonded in an autoclave at high temperature and high pressure to obtain a laminated glass.

[0153] Here, the heating temperature in the heating zone was set to 220°C, the surface temperature of the glass after passing through the heating zone was set to 80°C, the heating time was set to 1 minute, and the clamping pressure was set to 3 kg / cm 2 The temperature in the autoclave was set to a maximum of 140°C and the pressure was set to 14 kg / cm 2 The heating and pressurizing time in the autoclave was set to a maximum of 30 minutes.

[0154] (2) Deformation test

[0155] A deformation test was performed using the obtained sample laminated glass.

[0156] Figure 2 A schematic diagram for explaining the deformation test is shown in . That is, in a dark room, a light source 5 (manufactured by Japan Technology Center Co., Ltd., S-Light SA160), a laminated glass 6 and a screen 7 are arranged in a straight line in such a manner that the horizontal intervals are 3000 mm and 1500 mm, respectively. Here, the height of the light source 5 is set to 600 mm, and the angle of the light is set to 20° from the horizontal upward. In addition, the height of the laminated glass 6 is set to 900 mm at the lowest position, and is set to an angle of 18° in such a manner that the screen side becomes higher, and is set in such a manner that the width direction of the intermediate film for the laminated glass is inclined from the light source to the screen. In addition, the angle of the screen 7 is set to vertical. It should be noted that the screen is white and does not produce shadows due to its own surface unevenness.

[0157] The transmission projection image projected on the screen 7 in this state was visualized by camera 8 (manufactured by FUJIFILM, FINEPIX F900EXR). The measurement conditions were: aperture f / 5.9, exposure time 1 / 8s, ISO800, focal length 42mm, no flash, image size 4608×3456 pixels. The captured image was reduced to 640×640 pixels and subjected to 8-bit grayscale processing.

[0158] After that, the text file of the grayscale image is output, and 35 intervals are continuously selected at intervals of 10 pixels in the vertical direction of the projected image. In each interval, a simple moving average (25 pixels) is taken in the vertical direction, and it is subtracted from the interval as the basic brightness, thereby implementing tilt correction. Furthermore, in order to smooth the brightness value, a simple moving average (5 pixels) is implemented for each interval. After calculating the dispersion value between 11 pixels in the vertical direction, the maximum value of all brightness dispersion values ​​in 35 places is calculated. The smaller the maximum value of the brightness dispersion value, the more the laminated glass can suppress deformation.

[0159] [Table 1]

[0160]

[0161] Industrial Applicability

[0162] According to the present invention, there can be provided an interlayer film for laminated glass capable of providing laminated glass in which occurrence of perspective distortion is suppressed, laminated glass using the interlayer film for laminated glass, and a method for producing the interlayer film for laminated glass.

[0163] Description of Reference Numerals

[0164] 1: Interlayer film for laminated glass

[0165] 2: Roll

[0166] 3: Test samples

[0167] 5: Light source

[0168] 6: Laminated glass

[0169] 7: Screen

Claims

1. An interlayer film for laminated glass, characterized in that: The maximum curvature of the thickness of the interlayer film for laminated glass in the width direction is 0.010 m -1 the following.

2. The interlayer film for laminated glass according to claim 1, characterized in that: The maximum value of the thickness difference in the width direction measured in a 150 mm section of the interlayer film for laminated glass is 15 μm or less.

3. A laminated glass, characterized in that: A laminated glass in which the interlayer film for laminated glass according to claim 1 or 2 is laminated between a pair of glass plates, wherein the maximum curvature of the thickness in the width direction of the interlayer film for laminated glass in the laminated glass is 0.004 m -1 the following.

4. A laminated glass, characterized in that: A laminated glass in which the interlayer film for laminated glass according to claim 1 or 2 is laminated between a pair of glass plates, wherein the maximum curvature of the thickness in the width direction of the laminated glass is 0.010 m -1 the following.

5. The laminated glass according to claim 4, characterized in that: The maximum curvature of the thickness of the laminated glass in the width direction is 0.003m -1 the following.

6. A method for producing an interlayer film for laminated glass, characterized in that: A method for producing the interlayer film for laminated glass according to claim 1 or 2, The method includes a step of using a lip method in which a surface of the interlayer film for laminated glass is provided with irregularities while a raw resin composition is extruded from an extruder. As the pipe head of the extruder, a pipe head having a straightness of 4 μm or less over a width of 1000 mm and a concavity of 2 μm or less over a width of 80 mm was used.

7. The method for producing an interlayer film for laminated glass according to claim 6, wherein: As the press roll, a press roll having a cylindricity of 4 μm or less was used.

Citation Information

Patent Citations

  • Interlayer for laminated glass and laminated glass

    JP2007331959A